Peer effects in risky choices among adolescents - Konstantin E. Lucks; Melanie Lührmann; Joachim Winter (Institute for Fiscal Studies (IFS), 2017)
This paper examines the distributional impact of increases to out-of-work transfers, increases to work-contingent transfers, and increases in higher rates of income tax over the whole of life. We find that, in contrast to what is implied by standard snapshot analyses, increases to work-contingent benefits are just as effective at redistributing resources to the lifetime poor as increases to out-of-work benefits. This has important implications for the equity-efficiency trade-off typically thought to apply to work-contingent transfers. However, we find that higher rates of tax on annually assessed income are an effective way of targeting the lifetime rich, as incomes are more persistent towards the top of the distribution. Our results illustrate the importance of moving beyond an exclusively snapshot perspective when analysing tax and transfer reforms.
Keywords: D03; D80; G02; C91; D81; 330; peer effects; assortative matching; social interaction; risk and loss aversion